Analisis Pembelajaran Jarak Jauh (online) Mahasiswa Calon Guru IPA di Kota Pekanbaru pada Masa Pandemi Covid-19 - Riki Apriyandi Putra; Nurdiansyah Nurdiansyah; Dedi Futra; Indra Primahardani (Journal of Natural Science and Integration, 2021)
This study aims to analyze Distance Learning (PJJ) online science teacher candidate students in Pekanbaru City during the Covid-19 Pandemic. This research is a survey research with the type of public opinion survey. Sampling was taken through purposive sampling method. The data collected is ordinal data via e-questionnaire (google form), through a summative response scale using a modified Likert scale with 4 answer choices. The results showed that the form of learning during the pandemic using various dominant applications were Google Meet (22.47%), Google Classroom (17.95%), Whatsapp (15.56%), and Schoology (11.70%). Online PJJ is not effectively carried out based on the availability of infrastructure, convenience and accessibility, difficulty in lecture materials, time, increased competence, and variety of courses. The implementation of PJJ is in accordance with the learning objectives because lecturers vary the use of applications, interactions run smoothly, and lecturers motivate students. The hopes of students for online PJJ are that there is a quota subsidy, the existence of priority courses, a willingness to explore various applications and the existence of sustainability after the pandemic. The cause of online PJJ is not effective is because it is not supported by several things, namely changes in the mindset and motivation of the implementers (lecturers and students), limited infrastructure such as internet networks, tools (multitasking laptops / devices), and the readiness of institutional technology (platform and management learning. system, systematic and comprehensive learning planning, effective and efficient implementation (easily accessible and learned), learning culture, e-learning pedagogy, and academic atmosphere, technical training and user level of mastery, and time management.Keyword: science pre-service teacher, pandemic covid-19, distance learning ABSTRAKPenelitian ini bertujuan untuk menganalisis Pembelajaran Jarak Jauh (PJJ) online mahasiswa calon guru IPA di Kota Pekanbaru pada masa Pandemi Covid-19. Penelitian ini merupakan penelitian survey dengan jenis public opinion survey. Pengambilan sampel melalui metode purposive sampling. Data yang dikumpulkan adalah data ordinal melalui e-kuesioner (google form), melalaui summative response scale dengan menggunakan skala Likert yang dimodifikasi dengan 4 pilihan jawaban. Hasil penelitian menunjukan bahwa bentuk pembelajaran selama pandemi menggunakan berbagai aplikasi yang dominan adalah Google Meet (22,47%), Google Classroom (17,95%), Whatsapp (15,56%), dan Schoology (11,70%). PJJ online tidak efektif dilakukan berdasarkan ketersediaan sarana prasarana, kemudahan dan aksesibiltas, kesukaran materi perkuliahan, waktu, peningkatan kompetensi, dan ragam matakuliah. Pelaksanaan PJJ sudah sesuai dengan tujuan pembelajaran karena dosen memvariasikan penggunaan aplikasi, interaksi berjalan dengan lancar, dan dosen memotivasi mahasiswa. Harapan mahasiswa terhadap PJJ online adalah adanya subsidi kuota, adanya prioritas matakuliah, kemauan mendalami berbagai aplikasi dan adanya keberlanjutan setelah pandemi. Penyebab PJJ online tidak efektif adalah karena tidak disupport oleh beberapa hal, yaitu perubahan mindset dan motivasi pelaksana (dosen dan mahasiswa), keterbatasan sarana prasarana seperti jaringan internet, tools (laptop/gawai yang multitasking), dan kesiapan teknologi institusi (platform dan learning manajemen system, perencanaan pembelajaran yang sistematis dan komprehensif, pelaksanaan yang efektif dan efisien (mudah diakses dan dipelajari), budaya belajar, pedagogi         e-learning, dan atmosfer akademik, pelatihan teknis dan tingkat penguasaan pengguna, dan manajemen waktu.Kata kunci: mahasiswa calon guru IPA, pandemi Covid-19, pembelajaran jarak jauh (online).